LNG (LIQUEFIED NATURAL GAS): PROSPECTS FOR PRODUCTION AND USE IN REGIONAL SOCIO-ECONOMIC SYSTEMS - E. Shorov; A. Gladilin; N. Ryabukhin (Вестник Северо-Кавказского федерального университета, 2022)
The article presents the priority tasks and the main directions of the development of liquefied natural gas, based on the regional socio-economic system. Carried out the prospects of LNG production and consumption in the North Caucasus and Southern Federal Districts. Based on the analysis of the state and development of the industry, the authors of the article proposed a site for the placement of an LNG complex, as well as a layout of automobile gas stations for refueling LNG in the North Caucasus Federal District and the Southern Federal District. Special attention is paid to the use of liqueied natural gas as a motor fuel. The target segments of LNG consumption are justified.